Nutrient Requirement and Fertilizer Management for Agarwood Plantations: A Review - Muhamad Fahmi Yunus; Mohd Syahmi Salleh; Md Hoirul Azri Ponari; Paramita Cahyaningrum Kuswandi; Mohd Syafik Mohamad Hamdan (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2024)
Agarwood is a highly valued fragrant wood and has been traded for its economic and medicinal value. The resin in agarwood is used to produce high value downstream products such as fragrances, oils, medicines, teas, cosmetic carvings, and luxury goods where the demand for these products remains consistent. Most of the agarwood-producing trees come from the genera of Aquilaria and Gyrinops, which belong to the Thymelaeaceae (Malvales) family. In addition, Aquilaria malaccensis and Gyrinops versteegii are the most cultivated agarwood producing trees in Malaysia and Indonesia, respectively. Nevertheless, the survival of the species is threatened by the overharvesting of the forest, which leads to strict regulation by the exporting nations for international trade. Interestingly, agarwood plantation is a viable option which able to generate income for local population without causing any harm to the ecosystems. However, a lack of research on seedling preparation for large-scale plantations, and the optimum nutrient management practices have slowed down the agarwood industry. Hence, this review article will highlight the most effective strategy for enhancing agarwood cultivation by focusing on proper nutrient management to boost agarwood production.